Caracterização dos meios morfodinâmicos na bacia hidrográfica do córrego são José - Ituiutaba/MG - Venceslau, Fabio Reis (2020)
The landscape of a certain watershed expresses a series of marks and records that can be read and interpreted by society. This reading often allows researchers to better understand the interrelationship between the dynamics of society and nature and the effects and responses of the environment in the face of this anthropic intervention. Thus, when this anthropic intervention occurs in a disorderly manner and does not respect the dynamics of natural (physical) processes, degraded landscapes and unstable morphodynamic media can be generated, vulnerable to manifestations of erosion, flooding, overflowing, spate, silting of river channels, soil loss, induced fires, among others. In this context, the main objective of this research was to analyze the morphodynamics of the landscape that contemplates the watershed of São José stream, located in the urban area of the county of Ituiutaba-MG. Therefore, the study on Ecodynamics prepared by Tricart (1977) was used as one of the theoretical and methodological references. Thus, the following methodological procedures were used: a) Literature review on the main covered concepts; b) Preparation of thematic maps, such as the location of the area, lithology, pedology, hypsometry, slope, hydrography, geomorphometric parameters and land use and coverage, which supported the characterization of the study area; c) Fieldwork to support the characterization and investigation of thematic mappings; e) To make it possible to study the watershed's morphodynamic media (unstable, intermediate and stable), a summary table of the characteristics of the morphodynamic media was proposed, based on the classification of Tricart (1977). Besides, six representative points in the hydrographic basin were selected, in which the characterization and integrated analysis of the landscape was observed in more detail. As a result, several thematic cartographic products were generated, whose geomorphological map was the basis for the analysis of the morphodynamics of the watershed’s landscape, from the anaglyph method using three-dimensional images, photointerpretation and saved images from Google Earth, three geomorphological compartments were identified. The first was identified as smooth wavy tops of the hills, areas of concave, convex and rectilinear slopes, the valley bottoms in V and alluvial plains and alveoli, finally the narrow tops of the board form-type reliefs. The study on the relief showed that the predominant forms in the watershed are the hills with wide convexed tops and some board form-type reliefs in the higher areas. Regarding the landscape morphodynamics of the area, it was possible to observe that the anthropic interference in the land use and cover issue had a significant role in the classification othe unstable morphodynamic environment, mainly because the alteration of the geomorphological aspects (cuts in the ramp length of the slopes to form embankments, rectification in some slope segments and in the top areas) modify the shape of the river channels by waterproofing and rectifying the river bed, removing the vegetation cover from the land leaving the soil exposed to the weather. The results obtained regarding the 6 analyzed points in the watershed referring to the morphodynamic media were the following ones: 3 points were classified as intermediate, 2 points as unstable and 1 stable morphodynamic media. It was found that the presence of vegetation is a fundamental factor to identify a stable morphodynamic environment, since it can favor the infiltration over the surface runoff, favoring pedogenesis over watershed morphogenesis.